VD_FINDINFO HC / 2010 / 616 vom 4. August 2010 - VD Tribunal cantonal (2010)
PRESCRIPTION, RÉPÉTITIONENRICHISSEMENT ILLÉGITIME, BAIL À LOYER, FRAIS ACCESSOIRES | 257a CO, 67 al. 1 CO, 67 CO, 444 CPC, 445 CPC, 451 ch. 3 CPC, 452 al. 2 CPC, 452 CPC, 465 al. 1 CPC, 13 LTB